Differential effects of estrogen/androgen on the prevention of nonalcoholic fatty liver disease in the male rat - Zhang, Hua (The American Society for Biochemistry and Molecular Biology, 2013)
It is important to clarify the distinct contributions of estrogen/estrogen receptor (ER) and androgen/androgen receptor (AR) signaling and their reciprocal effects on the regulation of hepatic lipid homeostasis. We studied the molecular mechanisms underlying the preventive effects of estradiol (E2), dihydrotestosterone (DHT), or E2+DHT on high-fat diet-induced nonalcoholic fatty liver disease (NAFLD) in an orchidectomized Sprague-Dawley (SD) rat model. E2 is shown to be associated with decreased fatty acid synthesis in hepatic zone 3-specific manner by increasing the phosphorylation of acetyl coenzyme-A carboxylase via an ERα-mediated pathway. DHT is shown to be associated with decreased lipid accumulation and cholesterol synthesis in a hepatic zone 1-specific manner by increasing expression of carnitine palmitotyltransferase1 and phosphorylation of 3-hydroxy-3-methyl-glutaryl-CoA reductase via an AR-mediated pathway. E2+DHT showed an additive positive effect and normalized all three impaired zones of the liver. Gene expression changes in human severe liver steatosis were similar to those of experimental rat NAFLD. Steroids reversed the histopathological NAFLD changes, likely by decreasing fatty acid and cholesterol synthesis and increasing β-oxidation. The diverse steroid effects (ER/AR) on NAFLD prevention in male rats indicate the potential applicability of ER/AR modulators for NAFLD treatment.